PENYULUHAN ZAT ADIKTIF PADA MAKANAN DAN DAGUSIBU OBAT DI DESA BATU AMPA, KOTO TANGAH 50 KOTO - Elidahanum Husni; Septia Chandra Kessi (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
The purpose of this study was to describe the experience and exposure regarding the deployment of science have been obtained while in College, as well as dig potential in society, solve a problem that occurs in the community. The methods used are surveys and direct observation of spaciousness. Based on a survey that has been carried out beforehand, nagari Koto Tangah consists of 6 jorong with potential. At jorong Koto Tangah, tambun ijuak and across the ditch, and the stone tanyuah the society more farmed and worked disawah, it also reflected the views of his area filled with dykes-dykes. Jorong piladang includes a very advanced jorong and widest jorong other, society dijorong this many have business perternakan chicken and also as a trader. Jorong Sungai Cubadak is jorong who became the center of my attention, because every home at jorong is the same activities, i.e. have an attempt made crackers and become a supplier of crackers to various areas, such as to Bukittinggi, Payakumbuh and surrounding areas. However, besides communities often do not realize the importance of health and hygiene. The community is very fall asleep by job or daily. So, I as a student from the Department of Pharmacy health engaged in felt responsible for delivering and tell health information to the community. From my observations during the KKN in Nagari Koto Tangah, my eyes are bothered by having flashy colors on crackers results home industry are sometimes just left just lying dried dijalanan which is full of pollutants. Therefore I have an extra dangerous substances introduction program on food (addictive substances). And I also tried to give the knowledge of "Dagusibu" (get, use, save, Waste), so that the public know about the way the management of medication that is good and right.